Interface fluid syndrome after small incision lenticule extraction surgery secondary to posner schlossman syndrome - A case report - Dilinigeer Mokumu; Wenfei Hu; Ailifeire Damaola; Junshu Wu (Heliyon, 2023)
Purpose: This report describes a case of interface fluid syndrome (IFS) secondary to Posner Schlossman Syndrome (PSS) following small incision lenticule extraction (SMILE) surgery. Case presentation: A 19-year-old male was diagnosed with IFS secondary to PSS in his left eye 1 month after undergoing SMILE. Detailed patient history and clinical findings, auxiliary examination results, and short-term follow-up are reported. In this patient, the IFS was caused by elevated intraocular pressure (IOP) due to PSS. Treatment with topical steroids in combination with anti-glaucoma drops led to complete regression of the fluid, and there was no recurrence during a 7-month follow-up period. Conclusion: IFS is a potential complication of SMILE, and anterior segment ocular coherence tomography (AS-OCT) can definitively diagnose the condition. This case demonstrates that the treatment for IFS should be based on the underlying cause, and requires prompt and vigorous management for resolution.